2016
DOI: 10.1002/slct.201600449
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II)‐catalyzed Enantioselective α‐Hydroxylation and α‐Chlorination of β‐Ketoesters with N,N,O‐Tridentate Chiral Phenanthroline Ligand

Abstract: The N,N,O-tridentate chiral phenanthroline ligand was employed for Cu(II)-catalyzed enantioselective a-hydroxylation of b-ketoesters with racemic Davis' oxaziridine to provide the corresponding product. We also tried to understand the plausible mechanism for asymmetric induction of this reaction, achieved by the effective shielding of prochiral Cu(II) enolate. With this working hypothesis, enantioselective a-chlorination of b-ketoesters to give the corresponding products was achieved with high enantioselectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Typically, the weakly basic metal acetate complexes showed greater catalyst activity than those complexes prepared from neutral metal chlorides or Lewis acidic metal salts. Other chiral ligands were also examined for applicability to the Zn(OAc) 2 -catalyzed reaction (entries [11][12][13][14]. The trinuclear-aminoiminoBINOL (L2)-Zn 3 (OAc) 4 complex, which possessed outstanding catalytic activity for the iodolactonization reaction, gave 2a in 41% yield with 21% ee (entry 11) [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the weakly basic metal acetate complexes showed greater catalyst activity than those complexes prepared from neutral metal chlorides or Lewis acidic metal salts. Other chiral ligands were also examined for applicability to the Zn(OAc) 2 -catalyzed reaction (entries [11][12][13][14]. The trinuclear-aminoiminoBINOL (L2)-Zn 3 (OAc) 4 complex, which possessed outstanding catalytic activity for the iodolactonization reaction, gave 2a in 41% yield with 21% ee (entry 11) [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetric chlorination of β-ketoesters was described by Togni et al using a Lewis acid catalyst TiCl 2 (TADDOLato) in 2000 [3,4]. After seminal work by Jørgensen's bisoxazoline-copper catalysis [5], various metal-catalyzed enantioselective chlorinations of β-ketoesters have been developed using Cu [6][7][8][9][10][11][12][13], Ni [14], Co [15], Zn [10], Pd [16], and Fe [17]. The use of Cu and Zn salts for a single chiral ligand allows a switch in enantioselectivity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorination products 13 ( a – p ) are known from the literature, and their analytical data (NMR spectra and MS) fully matched those reported previously in the literature. 13 , 17 , 19 21 …”
Section: Methodsmentioning
confidence: 99%
“…Absolute configuration was determined by comparison of the retention times and the [α] D value with reported data. 21 …”
Section: Methodsmentioning
confidence: 99%
“…This reaction provides the most straightforward access to the α-hydroxy-β-dicarbonyl, an intriguing moiety commonly found in various biologically active natural products, agrochemicals, and pharmaceuticals [25][26][27]. Notably, a number of chemical protocols are available to accomplish this oxidation to yield product 2 [28][29][30][31][32][33]. For instance, Lu et al reported a Brønsted acid catalytic method with nitrosobenzene as the oxygen source [28], and Meng and co-workers documented a Zr(IV)/organic peroxide system [30].…”
Section: Introductionmentioning
confidence: 99%